2003
DOI: 10.1002/mpo.10312
|View full text |Cite
|
Sign up to set email alerts
|

Local control of parameningeal rhabdomyosarcoma: Outcomes in non‐complete responders to chemoradiation

Abstract: Surgical salvage after an incomplete response to chemoradiation in PM-RMS is feasible and can be curative in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…10,11,34,35 Conclusion Paediatric rhabdomyosarcoma of the nose and paranasal sinuses is an aggressive tumour with a poor prognosis. Second-line chemotherapy and radiotherapy are the main modalities, but have increased toxicity and low efficacy (due to resistance to chemotherapeutic agents and decreased tissue tolerance).…”
Section: Discussionmentioning
confidence: 99%
“…10,11,34,35 Conclusion Paediatric rhabdomyosarcoma of the nose and paranasal sinuses is an aggressive tumour with a poor prognosis. Second-line chemotherapy and radiotherapy are the main modalities, but have increased toxicity and low efficacy (due to resistance to chemotherapeutic agents and decreased tissue tolerance).…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases from HNRMS are rare and are mostly seen in patients with recurrent disease and distant metastatic disease in other parts of the body [46]. Imaging of the brain in search for brain metastases therefore is recommended only in clinically suspected patients [47].…”
Section: Staging Hnrmsmentioning
confidence: 99%
“…10 Few studies have described the surgical treatment of parameningeal sarcomas. Paulino et al 11 and Blatt et al 12 reported surgical resection in children with parameningeal rhabdomyosarcomas and partial response to chemoradiation. They both concluded that salvage surgery after insufficient response to chemotherapy is sometimes feasible and curative.…”
Section: Discussionmentioning
confidence: 99%